Public Perceptions about the Service Marketing Mix, Values and Trust in General Hospital - Pasaribu, Fajar; Astuty, Widia (Budapest International Research and Critics University, 2021)
Hospitals in Indonesia in responding to service marketing, are far behind from neighboring countries, management problems, unfinished service standards, accreditation, dissatisfaction with service quality and others. This study aims to determine and prove empirically: the effect of service marketing mix performance and service value on patient trust, either partially or simultaneously. The object and scope of this research is the service marketing mix, service value and trust. While the research method used in this research is explanatory research method. The population and the unit of analysis were inpatients in class B private general hospitals, totaling 10 hospitals in the city of Medan, North Sumatra province, amounting to 200 people.Determination of the sample using the principle of random sampling, ie each member of the population has the same opportunity to be selected as a sample. NextSampling for this study was based on Yamane's sample size. The analysis used in this study is path analysis with the help of the SPSS application. This research resulted in findings in the form of developing the dimensions of the marketing mix from 7-Ps to 9-Ps, with the addition of professional dimensions and employee appearance. In general, from the results of the study, patients judged that the performance of the RSU's marketing mix was not entirely in line with patient expectations, including product, promotion and professional dimensions. The discrepancy between the dimensions of the product and the patient's expectations, because the services provided by the type of treatment class are different from the patient's perception, as is the case with doctor's consultation services. The discrepancy between the dimensions of promotion and patient expectations is due to a lack of information on the type of service.